Wave Wash and Its Effects in Ship Design and Ship Operation: A Hydrodynamic Approach to Determine Maximum Permissible Speed in a Particular Shallow and Narrow Waterway. (2017) - Saha, Goutam Kumar; Abdullah, Mohammad Sayem Bin; Ashrafuzzaman, Mohammad
Abstract: Wave wash is a hydrodynamic tool which explains ship generated waves and its impacts on shore and shore erosion. This paper describes that wave wash is an important factor to impose ship speed restriction and selecting speed for any shallow and narrow waterway. Relationships among ship speed, water depth, wave height, time period and wave energy have been established. Speed and depth conditions have been classified into four groups: Sub-Critical ( Fh < 0.75), Trans-Critical (0.75 < Fh < 1.0), Critical ( Fh = 1.0) and Super-Critical ( Fh > 1.0). It is focused on waves generated by the ships to observe the maximum permissible speed for a vessel operated in a particular shallow and narrow water way. Empirical Formulae have been employed to find out maximum wave heights in relation with ship generated wave period, speed and other parameters. Maximum theoretical wave heights have been compared with wave wash criteria. These wave heights have also been compared with CFD results from potential flow solver and some commercial software. A case study has been done for a particular shallow and narrow waterway of Bangladesh. A vessel operated in that particular waterway had been selected for observing wave wash phenomena. Comparisons among theoretical results from different empirical equations, CFD results and different speed ranges have been done on which a model has been proposed to determine highest permissible ship speed in a shallow and narrow waterway. When a ship moves around critical speed range, wave wash becomes dominant.